ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA FASE A MENGGUNAKAN KETERAMPILAN COMPUTATIONAL THINKING TERHADAP BERPIKIR KRITIS BERBANTUAN BAWAGASING - Prasetyo, Eko; Mariana, Neni; Wiryanto, Wiryanto (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This study aims to improve the critical thinking skills of Phase A students of SDN Mojoruntut 3 Krembung District, Sidoarjo Regency through the application of the Computational Thinking approach using BAWASING (Balok Warna-Warni Gampang Asik). The research subjects were Phase A students of SDN Mojoruntut 3 with a total of 15 students and the object of research was students' critical thinking skills. The research method used This research is a descriptive qualitative research with a survey method on Phase A students at SDN Mojoruntut 3 Kec.Krembung Kab.Sidoarjo with a total of 15 students. observation. The data or information collected in this study is in the form of qualitative data. The type of data used by researchers is the level of Computational Thinking of Phase A students using BAWAGASING (Easy Asik Color Blocks). The results showed that of the 15 students tested, it was stated that 7 students were in the very good category, 5 students were in the good category, there were 3 students in the sufficient category. In the application of BAWAGASING (Colorful Blocks Easy Asik) no students were found in the low and very low categories which means 0 students. The limitations in this study are that students are only tested in one material, namely the shape and color of the building space, researchers only conduct at a limited level and do not use the effectiveness test. For other researchers, it is expected to conduct tests with colorful blocks that cover a wider range of material, for example, on the formulas of space buildings and can be tested at a wider level by comparing various kinds of phase A students in many schools and conducting effectiveness tests using research software such as SPSS and so on.